1,3-Dipolar Cycloaddition of Diazophosphonates with Methyl(Ethyl) Acrylate for the Synthesis of 5-Arylpyrazole-3-carboxylates - Zinovyev, Nikolay A.; Beletskaya, Irina P.; Titanyuk, Igor D. (Synthesis, 2024)
A wide range of α-aryl-α-diazophosphonates were easily prepared via modified diazo transfer reaction. Benzylphoshonates reacted with tosyl azide (TsN3) in the presence of potassium tert-butoxide (KOtBu) to afford diazophosphonates in yields up to 93% (generally 70–80%). Aryldiazophosponates were successfully explored for the synthesis of 5-aryl-substituted pyrazol-3-carboxylates in one pot by the 1,3-dipolar cycloaddition with alkyl acrylates followed by NaH treatment. The second stage led to elimination of the diethoxylphosphoryl moiety with the aromatization of cycle.
Keywords: diazo compounds; diazophosphonates; 1,3-cycloaddition; pyrazoles; diazo transfer